Strain hardening of Hadfield high manganese steels. (2022) - Hai, Nguyen Hong; Trung, Nguyen Danh; Khanh, Pham Mai; Dung, Nguyen Huu; Long, Bui Duc
Abstract: Hadfield manganese steels have high impact capacity, which has been widely used in many applications such as jaw crushers, rail tracks, dredge buckets, tank chains etc. Aim of this research is to study the effects of strain hardening on the microstructure and mechanical properties of austenitic manganese steels. The Hadfield high manganese steels were modified using FeTi70 at different temperatures of 1500, 1550 and 1600 °C. The modified steels were heat-treated by two steps process, and then strained hardening by ball impact in a large ball container with a diameter of 2 m under the rotation speed of 60 rpm for different duration of 5, 10 and 20 h. The results showed that the density of twining and thickness of deformed surfaces increased with the impact duration. Hardness of deformed surfaces was significantly increased from 430 Hv to a maximum value of 510 Hv, whilst that of inside undeformed regions are unchanged at 280 Hv. A minimum intensity of weight loss of 0, 245 kg × 10 −9  /Nm achieved for the modified sample at temperature of 1500 °C.